Quiet dell : a novel - Phillips, Jayne Anne, 1952- (Scribner, 2013)
In 1931, Emily Thornhill, one of the few women in the Chicago press, covers the murders of Asta Eicher and her three children and, obsessed with finding out what happened to this beautiful family, allies herself with the man funding the investigation.